SANKSI PIDANA TERHADAP TINDAK PIDANA PENCEMARAN UDARA DITINJAU DARI UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP : MURLINUS - Murlinus (LPPM STIA Nusantara Sakti, 2021)
Scientific papers has to know language criminal sanctions against crime air pollution in perspective Constitution Nomber 32 Year 2009. This research a library research with lenguage approach constitution as will as method collection data through study literarature. Based on this research which is conducted results obtained and conclusion that air pollution especially what happened jambi throughout the year 2019 is the crime detrimental wide community, and the action with constitution number 32 year 2009, Protection and management environmend. That matter caused law awarenes publik as well as the absence law enforcement that what happens. Othen than that the act that causes pollution and damaging the environment. Therefore pollution action air normatively juridical on the contrary to constitution ang criminal law.Based on that conclusion as a government 0fficial expected to improve oversight and enforce law applicable so that it doesn’t happen enhancement air pollution, specifically caused by burning forest and land.